Introduction to Yogyakarta Icons in The Game of Running Challenge - Bonai, Angga Adha Nugroho; Nugraheny, Dwi; Agustian, Harliyus (Sekolah Tinggi Teknologi Adisutjipto Yogyakarta, 2019)
Yogyakarta's strong culture makes Yogyakarta one of the tourist areas frequented by tourists, both foreign tourists and local tourists. The Visitors come from various groups, for example visitors who come with family or individuals. A game model is needed that can facilitate the child in remembering the tourist icons in Yogyakarta through a Game Running Challenge that is made as attractive as possible and can run on the Windows operating system. The game running challenge application can provide convenience to users who are children aged 6-10 years to get to know and know the most famous icons in Yogyakarta through a game. So that it can be an educational medium that has a pattern of learning by doing learning.